An economic assessment of biogas production and land use under the German renewable energy source act - Ruth Delzeit; Wolfgang Britz (Kiel Institute for the World Economy (IfW), 2012)
The Renewable Energy Source Act (EEG) promotes German biogas production in order to substitute fossil fuels, protect the environment, and prevent climate change. As a consequence, green maize production has increased significantly over the last years, causing negative environmental effects on soil, water and biodiversity. In this paper we quantitatively analyse the EEG-reform in 2012 by applying the simulation tool ReSI-M (Regionalised Location Information System - Maize). Comparing the EEG 2012 with a former version of the legislation, results imply that the reform contributes to an expansion of biogas electricity generation compared to former versions, and thus to substitution of fossil fuels. Furthermore, given a restriction in the share of green maize input, its production is reduced and the crop-mix is diversified. However, since maize provides the highest energy output per area, total land requirement for biogas production increases. An alternative analysis shows that an EEG with tariffs independent from plant-types would provide the highest subsidy-efficiency, but slightly lower land efficiency compared to the EEG 2012.
More recent version: http://hdl.handle.net/10419/130546
Keywords: C61; Q16; Q42; 330; bioenergy; biogas; land use; policy analysis; simulation model; Förderung regenerativer Energien; Bioenergie; Wirkungsanalyse; Maisanbau; Landwirtschaftliche Bodennutzung; Deutschland